Riprese aeree innovative per le emergenze - Garnero, Gabriele (GEOmedia, 2016)
The significant spread of technologies, like those to bring the photogrammetric sensors carried by drones, for the acquisition of spatial information in cartography during emergency situations, confirmed the successful application considering peculiarities reason, such as cost, speed and flexibility of use.